Rainbow six - Clancy, Tom (New York : G. P. Putnam's Sons, 1998)
Former Navy SEAL John Clark leads a Europe-based special force composed of international agents to combat terrorism. The force tackles the occupation of a Swiss bank, an amusement park massacre and eco-terrorism.
Keywords: Terrorists -- Fiction; Action and adventure fiction